Comparison of the 1-year survival rate in infants with congenital heart disease diagnosed by prenatal and postnatal ultrasound: A retrospective study. Issue 4 (29th January 2021) - Han, Bing; Tang, Yi; Qu, Xueling; Deng, Chuanjun; Wang, Xing; Li, Jie
Abstract : Abstract: The impact of prenatal diagnosis on the survival outcome of infants with congenital heart disease (CHD) is still unclear. This study aimed to compare the 1-year survival rate between the prenatally and postnatally diagnosed infants with CHDs. A single-center population-based retrospective cohort study was performed on data from all infants diagnosed with CHD born between January 1998 and December 2017. Among infants with isolated CHDs, the 1-year Kaplan–Meier survival probabilities for prenatal and postnatal diagnosis were estimated. Cox proportional hazard ratios were adjusted for critical CHD (CCHD) status and gestational age. A total of 424 (40 prenatally and 384 postnatally) diagnosed infants with CHDs were analyzed. Compared with non-CCHDs, infants with CCHDs were more likely to be prenatally diagnosed (55.0% vs 18.0%; P < .001). Among the 312 infants with isolated CHDs, the 1-year survival rate for the prenatally diagnosed was significantly lower than postnatally diagnosed (77.1% vs 96.1%; P < .001). For isolated CCHDs, the 1-year survival rate for the prenatally diagnosed was significantly lower than postnatally diagnosed (73.4% vs 90.0%; P < .001). The 1-year survival rate was increased with the increase of age at diagnosis. Among infants with isolated CHDs and CCHDs, the adjusted hazard ratios for 1-year mortality rates for the prenatally versus postnatally diagnosed were 2.554 (95% confidence interval [CI], 1.790, 3.654; P < .001) and 2.538 (95% CI: 1.796, 3.699; P < .001), respectively. Prenatal diagnosis is associated with lower 1-year survival rate for infants with isolated CCHDs. This could probably due to variation in the disease severity among the CCHD subtypes.